Fat-Derived Stromal Vascular Fraction Cells Enhance the Bone-Forming Capacity of Devitalized Engineered Hypertrophic Cartilage Matrix. (26th July 2016) - Todorov, Atanas; Kreutz, Matthias; Haumer, Alexander; Scotti, Celeste; Barbero, Andrea; Bourgine, Paul E.; Scherberich, Arnaud; Jaquiery, Claude; Martin, Ivan
Abstract : This study tested the hypothesis that freshly harvested stromal vascular fraction cells from human adipose tissue enhance engineered and devitalized hypertrophic cartilage remodeling into bone tissue. Abstract : Abstract : Engineered and devitalized hypertrophic cartilage (HC) has been proposed as bone substitute material, potentially combining the features of osteoinductivity, resistance to hypoxia, capacity to attract blood vessels, and customization potential for specific indications. However, in comparison with vital tissues, devitalized HC grafts have reduced efficiency of bone formation and longer remodeling times. We tested the hypothesis that freshly harvested stromal vascular fraction (SVF) cells from human adipose tissue—which include mesenchymal, endothelial, and osteoclastic progenitors—enhance devitalized HC remodeling into bone tissue. Human SVF cells isolated from abdominal lipoaspirates were characterized cytofluorimetrically. HC pellets, previously generated by human bone marrow-derived stromal cells and devitalized by freeze/thaw, were embedded in fibrin gel with or without different amounts of SVF cells and implanted either ectopically in nude mice or in 4-mm-diameter calvarial defects in nude rats. In the ectopic model, SVF cells added to devitalized HC directly contributed to endothelial, osteoblastic, and osteoclastic populations. After 12 weeks, the extent of graft vascularization and amount of bone formation increased in a cell-number-dependent fashion (up to, respectively, 2.0-fold and 2.9-fold using 12 million cells per milliliter of gel). Mineralized tissue volume correlated with the number of implanted, SVF-derived endothelial cells (CD31+ CD34+ CD146+). In the calvarial model, SVF activation of HC using 12 million cells per milliliter of gel induced efficient merging among implanted pellets and strongly enhanced (7.3-fold) de novo bone tissue formation within the defects. Our findings outline a bone augmentation strategy based on off-the-shelf devitalized allogeneic HC, intraoperatively activated with autologous SVF cells. Significance : This study validates an innovative bone substitute material based on allogeneic hypertrophic cartilage that is engineered, devitalized, stored, and clinically used, together with autologous cells, intraoperatively derived from a lipoaspirate. The strategy was tested using human cells in an ectopic model and an orthotopic implantation model, in immunocompromised animals.